Ototoxicity Associated with Oxaliplatin in a Patient with Pancreatic Cancer - Oh, Sun Young; Wasif, Nawal; Garcon, Marie Carmel; Rodriguez, Gladys; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Context Oxaliplatin, a third-generation platinum derivative is commonly used for the treatment of colorectal cancer, pancreatic cancer, upper gastrointestinal cancer, hepatobiliary cancer, and ovarian cancer. Neurotoxicity is the dose limiting toxicity and ototoxicity is very rare, less than 1% of patients. Case report We present a case of a female patient with locally advanced unresectable pancreatic cancer who developed hearing loss after receiving oxaliplatin and gemcitabine. The dose of oxaliplatin was reduced but continued due to clinical benefit and radiological response. Discussion To the best of our knowledge, this is the third case report of oxaliplatin-induced ototoxicity. Ototoxicity seems to be a rare complication of oxaliplatin therapy. Regardless of its rare occurrence, clinicians should be aware of this severe complication and be diligent in monitoring patients’s clinical symptoms. Image: Post-oxaliplatin audiogram.